A Study on Mechanical and Microstructural Characteristics of Concrete Using Recycled Aggregate - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The objective of this paper is to provide a comprehensive study about the performance of concrete using mixed coarse recycled aggregate (MCRA) as an alternative for natural aggregate (NA) at replacement levels of 0, 30, 60, and 100%, which can greatly reduce the environmental pollution by incorporating the construction and demolition wastes in the reproduction of concrete. The focus of this study was to use the raw MCRA that was directly obtained from a recycling plant and not further processed. Initially, MCRA was studied to ascertain if its property meets the recommended Indian standards for natural aggregates. Using the slump test, the workability of freshly prepared concrete with a characteristic strength of 30 MPa was assessed. Additionally, the mechanical performance of concrete was assessed on the specimens prepared in the different forms: cubes, cylinders, and beams. Moreover, Scanning Electron Microscopy (SEM) with EDAX, XRD, and FTIR were used to study the microstructural behavior of selected optimum and control mixes at 7 and 28 days of curing. The studies revealed that a higher MCRA content improved the workability of concrete and 30% replacement of MCRA improved the compressive strength by 11.01, 6.98, 6.19, and 14.24% at 7, 28, 56, and 90 days respectively. At the same time, the 30% replacement of the MCRA mix showed an improved split tensile and flexural strength by 2.92 and 6.26%, respectively. The microstructural analysis showed that the optimum mixture had a more condensed microstructure. Therefore, 30% replacement of MCRA can be incorporated in the characteristic strength of concrete of 30 MPa. In particular, MCRA incorporation had a positive influence similar to conventional concrete on the physical, mechanical, and microstructural properties, which can increase the utilization of all kinds of directly obtained construction and demolition wastes to increase the circular economy in the construction sector. © 2022 by the authors.